Japan reaps the consequences of flawed rice policies - Godo, Yoshihisa; Yamauchi, Futoshi (East Asia Forum, 2025)
In response to soaring supermarket rice prices, the Japanese government released 210,000 tonnes of rice from its emergency reserves in February 2025, despite an abundance of rice production in the country. The price spike since summer 2024 did not occur because of a production shortage, but due to media coverage of extreme summer heat, panic buying after an earthquake warning, speculation and rigidities and missing markets in the rice system. A market-friendly approach could provide a more sustainable resolution than ad-hoc government actions.